(3eTcdI GdHWGdI aj eUQ hOhQ GdJTQjYGJ GdGLJeGYjI aj GdMO efgG (B/ s - (3S``jO Y``hV Y`dj Y`hVs; (3CMeO MSf GdHQYj (B: s; (3eMeO CMeO ESeGYjd (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2014)
(3dGTc Cf eTcdI GdHWGdI XGgQI YGdejI JYQagG GdOhd GdeJbOeI Ch GdfGejI Ydi MmO ShGA HOQLGJ eNJdaI(B. (3hfXQkG dJaGbegG ai eUQ (B- (3GgJeJ GdOQGSI HeYGdLJgG HUhQmI YdejmI hehVhYjI ; chfgG bVjI ef Cge GdbVGjG GdHGQRI ai GdeLJeY GdeUQi ; dCfgG djSJ eTcdI abW (B: (3hdcfgG CUHMJ XGgQI JYGfi efgG cd GdMcheGJ hGdeSFhdjf HcGaI JNUUGJge heLGd Yedge (B: (3MjK JMhdJ ef eTcdI GLJeGYjI hGbJUGOjI hbGfhfjI Edi eTcdI SjGSjI hbhejI ; hdPdc JYJHQ GdOQGSI eMGhdI dGbJQGM eYGjjQ efGSHI deYGdLI eTcdI GdHWGdI Yf WQjb ebJQMGJ hJhUjGJ ehVhYjI ddMO ef GdeTcdI(B: (3hef NdGd GbJQGM JYOjd GdbGfhf Ch EjLGO fUhU HOjdI JJhGcH hJJLGhH eY eYWjGJ GdhGbY heSJLOGJg GdSQjYI GdeJdGMbI (B. (3hddNQhL ef gPG GdeCRb cGf dGHO ef HMK OhQ GdJTQjYGJ GdGLJeGYjI ai GdMO ef GdHWGdI Ch GdhUhd HgG Edi GdeYOd GdeSehM Hg YGdejkG (B: (3hMHPG dh Cecf GdbVGA YdjgG Yf WQjb GdbhGfjf hCgegG GdbhGfjf GdGbJUGOjI (B: (3cbGfhf GdGSJKeGQ (B: (3hbGfhf GdVQGFH (B: (3hbGfhf GdfbO GdGLfHi (B: (3hbGfhf GdLeGQc (B: (3Ke jCJi HYO Pdc ai GdGgejI GdbhGfjf GdGLJeGYjI PGJ GdUdI HehVhY GdOQGSI (B: (3bGfhf GdYed(B: (3hbGf`hf GdJCejfGJ GdGLJeGYjI (B: (3hbGf`hf GdJYGhf(B: (3heYQaI eG EPG cGf dgPg GdbhGfjf Cf JSge ai GdMO ef gPg GdeTcdI (B: (3heOi edGAeJgG dEjLGHjGJ GdYhdeI hSdHjGJgG hGdfXGe GdYGdei GdLOjO s
This study aims to treat the unemployment case in Egypt with scientific and objective image by explain the social legislations role to reduce them, because this case is one of the important cases in Egyptian social. To achieve these objectives, we divided this research to three parts: Part I: the plight of unemployment in the world today, includes conception and types and the characterizes and dimensions of unemployment in Egypt. Part two: legislative means in the fight against unemployment representative in work measures international and Arab to reduce the unemployment in Egypt. The part three: dealt with means applied to the reduction of unemployment, where cooperation, small projects, sector irregular, syndicates and civil organizations and the immigration and its role in the unemployment reduce. The study ended with an conclusion dealt with all measures which face the unemployment cries by short- term procedures, which are rapid procedures et long-term procedures, which are late procedures.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2014.s
(3HHdjhLQGajG(B: (3UaMGJ(B357-374.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdHWGdIs; (3CfhGY GdHWGdIs; (3ecGaMI GdHWGdIs; (3GdhSGFd GdJTQjYjI aj ecGaMI GdHWGdIs; (3GdhSGFd GdJWHjbjI aj ecGaMI GdHWGdIs; (3GdMO ef GdHWGdIs; (3GdgLQIs; (3GdHWGdIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2014